Liquid Polydimethylsiloxane Grafting to Enable Dendrite‐Free Li Plating for Highly Reversible Li‐Metal Batteries. (27th May 2019) - Meng, Junwei; Chu, Fulu; Hu, Jiulin; Li, Chilin
Abstract: Li‐metal is considered as the most promising anode material to advance the development of next‐generation energy storage devices owing to its unparalleled theoretical specific capacity and extremely low redox electrochemical potential. However, safety concerns and poor cycling retention of Li‐metal batteries (LMBs) caused by uncontrolled Li dendrite growth still limit their broad application. Herein, liquid polydimethylsiloxane (PDMS) terminated by –OCH3 groups is proposed as a graftable additive to reinforce the anode dendrite suppression for LMBs. Such a grafting triggers the formation of a conformal hybrid solid electrolyte interphase (SEI) with increased fractions of LiF and Li–Si–O‐based moieties, which serve as a rigid barrier and ionic conductor for uniform Li‐ion flow and Li‐mass deposition. The grafting protected anode endows Li/Li symmetric cells with a long lifetime over 1800 h with a much smaller voltage gap (≈25 mV) between Li plating and stripping, than the naked anode. The coulombic efficiency values for Li/Cu asymmetric cells in carbonate electrolyte can reach up to 97% even at a high current density of 3 mA cm −2 or high capacity up to 4 mAh cm −2 . The liquid PDMS additive shows advantage over solid siloxane additives with poor grafting ability in terms of Li surface compaction and SEI stabilization. Abstract : Liquid polydimethylsiloxane is proposed as a graftable additive to reinforce anode dendrite suppression for Li‐metal batteries. Such a grafting triggers the formation of a conformal hybrid solid electrolyte interphase with increased fractions of LiF and Li–Si–O‐based moieties. The grafting protected anode endows symmetric cells with a long lifetime with a much smaller voltage gap between Li plating and stripping.